2016
DOI: 10.1101/gad.276725.115
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of prosurvival Bcl-2 proteins activates Bax/Bak through the outer mitochondrial membrane

Abstract: The mechanism of Bax/Bak activation remains a central question in mitochondria-dependent apoptotic signaling. While it is established that all proapoptotic Bcl-2 homology 3 (BH3)-only proteins bind and neutralize the antiapoptotic Bcl-2 family proteins, how this neutralization leads to Bax/Bak activation has been actively debated. Here, genome editing was used to generate cells deficient for all eight proapoptotic BH3-only proteins (OctaKO) and those that lack the entire Bcl-2 family (Bcl-2 allKO). Although th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
236
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(274 citation statements)
references
References 63 publications
17
236
0
8
Order By: Relevance
“…As the main members of the Bcl-2 family, Bcl-2, Bax and Bcl-xL mainly regulate the apoptosis of cells by affecting the mitochondrial pathway. When cells receive death signals, Bax, which is bound to Bcl-2 or Bcl-xL, is displaced, increasing the permeability of the mitochondrial membrane and leading to the release of a series of substances, thus eventually causing the death of cells (19).…”
Section: Discussionmentioning
confidence: 99%
“…As the main members of the Bcl-2 family, Bcl-2, Bax and Bcl-xL mainly regulate the apoptosis of cells by affecting the mitochondrial pathway. When cells receive death signals, Bax, which is bound to Bcl-2 or Bcl-xL, is displaced, increasing the permeability of the mitochondrial membrane and leading to the release of a series of substances, thus eventually causing the death of cells (19).…”
Section: Discussionmentioning
confidence: 99%
“…25 Cancer metastasis is the major reason for high mortality of to suppress anti-apoptotic impact. 30 Experiment results indicated that knockdown of PANDAR inhibited the levels of Bcl-2 and reinforced the levels of Bax. In other hand, previous studies suggested that epithelial mesenchymal transition (EMT) was one of important mechanism in cell migration and invasion.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…Of note, literally all known BH3-only proteins can be rendered to become direct activators at least in vitro, depending on experimental conditions (Du et al 2011;Chen et al 2015). Hence, it is even more surprising that this autoactivation also happens in the absence of any known BH3-only protein ever reported to be involved in mitochondrial apoptosis or autophagy (O'Neill et al 2016). While these studies do not completely exclude an accelerating or modulatory role of direct interaction of some BH3-only proteins with BAX or BAK in a given cellular-or stimulus-dependent context, it challenges the universal validity of the "direct activation/embedded together" models.…”
mentioning
confidence: 99%